Placental ultrastructural changes and apoptosis in pregnancies with meconium stained amniotic fluid [Mekonyumlu amnion sıvısı olan gebeliklerde plasental i̇nce yapısal deǧişiklikler ve apoptozis] - ÖZEK, EREN; TÜRKÖZ, HÜSEYİN KEMAL; BİLGEN, HÜLYA SELVA (Federation of Turkish Pathology Societies, 2012)
Objective: The cause of meconium stained amniotic fluid in term healthy pregnancies is not clearly understood yet. The aim of this study was to investigate the placental ultrastructural changes and placental apoptosis in pregnancies complicated with meconium stained amniotic fluid. Material and Method: The study group was composed of mothers (n: 13) and their term, appropriate for gestational age newborns with meconium stained amniotic fluid but without meconium aspiration syndrome. The control group consisted of mothers (n: 24) and their term appropriate for gestational age babies. We studied placental ultrastructural changes by transmission electron microscopy and placental apoptosis by transmission electron microscopy and the TUNEL method. Results: The incidence of placental apoptosis by the TUNEL method was significantly higher in the study group compared to the control group. Transmission electron microscopy investigation revealed more remarkable ultrastructural changes in the study group compared to the control group. Conclusion: The increased apoptosis and ultrastructural findings in placentas with meconium stained amniotic fluid may be related to the placental adaptation to the hypoxic fetuses.
Keywords: Apoptosis; Meconium; Placenta